2020
DOI: 10.1016/j.virusres.2020.197956
|View full text |Cite
|
Sign up to set email alerts
|

Integrin β3, a RACK1 interacting protein, is critical for porcine reproductive and respiratory syndrome virus infection and NF-κB activation in Marc-145 cells

Abstract: Although shared co-first author. Chao Yang performed more experiments than Rui Lan.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…ITGB3 (integrin subunit β3) is enriched in this pathway and plays a crucial role in coordinating immune responses, which is widely distributed in the spleen. Previous research has emphasized the positive correlation between ITGB3 and porcine PRRSV infection and transmission [60][61][62]. Among the three pig breeds, the expression level of the ITGB3 gene is highest in Ningxiang pigs and lowest in F 1 offspring.…”
Section: Discussionmentioning
confidence: 98%
“…ITGB3 (integrin subunit β3) is enriched in this pathway and plays a crucial role in coordinating immune responses, which is widely distributed in the spleen. Previous research has emphasized the positive correlation between ITGB3 and porcine PRRSV infection and transmission [60][61][62]. Among the three pig breeds, the expression level of the ITGB3 gene is highest in Ningxiang pigs and lowest in F 1 offspring.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we used miRNA sequences of chicken and zebra finch, which are available in miRbase, to search for conserved miRNAs and detected 437 known miRNAs. Similarly, several studies were also mapped to precursor/mature miRNAs of chicken or other animals in miRbase to annotate conserved miRNAs ( Cui et al., 2018 ; Wu et al., 2018 ; Wu et al., 2019a ; Yang et al., 2020 ). In addition, miRNA length showed that the majority had a length of 23 nt and the first nucleotide base revealed U predominance in the identified miRNAs ( Figure 2 ), which is consistent with the findings of other studies ( Chen et al., 2021 ; Zhang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Integrins act as entry receptors for multiple viruses, including ZIKV ( Seong et al., 2020 ), HIV ( Dalvi et al., 2016 ), and West Nile virus (WNV) ( Schmidt et al., 2013 ), and are also involved in immunity response ( Trentelman et al., 2020 ). Moreover, a recent study reported that ITGB3 plays an essential role in the activation of NF-κB and Porcine reproductive and respiratory syndrome virus (PRRSV) infection ( Yang et al., 2020a ). Accordingly, our data demonstrated that overexpression of ITGB3 promoted DHAV-1 replication.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread presence of a scaffolding protein receptor for activated protein kinase C1 (RACK1), which exhibits regulatory activity with protein kinase C (PKC) in both prokaryotes and eukaryotes, has garnered increasing attention and scrutiny [ 1 , 2 ]. As a highly conserved member of the tryptophan-aspartic acid domain (WD) repeat protein family, RACK1 participates in many biological processes, such as proliferation, cell migration, apoptosis, development, cellular adaptation processes, and immune responsiveness [ 1 , 3 , 4 , 5 , 6 , 7 , 8 ]. In addition, RACK1 is known as an adaptor protein in multiple intracellular signal transduction pathways, such as the PKC/RACK pathway [ 9 ], the cyclic AMP-specific phosphodiesterase pathway [ 10 , 11 ], the tyrosine kinase-phosphatase pathway [ 12 ], and the Aryl hydrocarbon receptor (AhR) signaling pathway [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%